Neighborhood socioeconomic status and segregation linked to cognitive decline. Issue 1 (8th February 2023) - Meyer, Oanh L.; Besser, Lilah; Tobias, Michele; George, Kristen M.; Gavett, Brandon; Farias, Sarah Tomaszewski; Bhagat, Nishi; Pham, My Le; Chrisphonte, Stephanie; Whitmer, Rachel A.
Abstract: Introduction: Few longitudinal studies have examined the joint impact of neighborhood segregation and neighborhood socioeconomic status (NSES) in cognitive decline over time. Methods: This study included non‐Hispanic White (NHW, n = 209) and Black participants ( n = 118) whose cognition was evaluated as part of an ongoing longitudinal study. Four distinct categories of segregation and NSES were evaluated for their association with cognitive outcomes (episodic memory, semantic memory, executive function, and spatial ability) using race‐specific mixed‐effects models. Results: Compared to Black participants living in higher segregation‐lower NSES areas, Black participants living in lower segregation‐lower NSES areas or higher segregation‐higher NSES areas experienced slower decline in episodic memory over time. Compared to NHW participants living in higher segregation‐lower NSES areas, NHWs living in lower segregation‐higher NSES areas experienced faster decline in spatial ability. Discussion: Segregation and NSES are differentially associated with cognition depending on participant race. Further research is needed to replicate study results.